2021
DOI: 10.18502/htaa.v4i1.5865
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Social Media During the COVID-19 Crisis: A Narrative Review

Abstract: In late 2019, the coronavirus 2019 (COVID-19) emerged in Wuhan, China, and rapidly spread around the world. Due to this incident, the use of social networks has increased among people. The present narrative review aimed to investigate the studies conducted on the subject of social media and COVID-19 in the Web of Science database. The investigations show that social media has been used to share viewpoints, health care, and distance learning during the COVID-19 crisis. Therefore, using social media can be a val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…This initiative was broadcasted on Lilaphalapha's Facebook page.The centrality of social media during this period cannot be overemphasised. Twitter, Facebook, YouTube, and Instagram are among the most important networks used throughout during the pandemic (Shoaei & Dastani, 2020). Shoaei and Dastani (2020) allude that the use of social networks increased during the period when coronavirus was spreading around the world.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…This initiative was broadcasted on Lilaphalapha's Facebook page.The centrality of social media during this period cannot be overemphasised. Twitter, Facebook, YouTube, and Instagram are among the most important networks used throughout during the pandemic (Shoaei & Dastani, 2020). Shoaei and Dastani (2020) allude that the use of social networks increased during the period when coronavirus was spreading around the world.…”
Section: Introductionmentioning
confidence: 99%
“…Twitter, Facebook, YouTube, and Instagram are among the most important networks used throughout during the pandemic (Shoaei & Dastani, 2020). Shoaei and Dastani (2020) allude that the use of social networks increased during the period when coronavirus was spreading around the world. During that period, social media experienced an influx of videos seeking to provide a picture to the world about what other nations were experiencing.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Indonesian Christian University has chosen social media platforms to share study materials and assignments with students after outbreak of COVID -19 (Nadeak, 2020). Similarly, study of Dalili and Dastain (2020) has found that social media has been used to share viewpoints and distance learning during the COVID-19 crisis. Why in pandemic period only?…”
Section: Introductionmentioning
confidence: 99%